Exploring the Perceived Effectiveness of ChatGPT in Enhancing Students' Vocabulary and Writing Style in Academic Writing - Khouloud HARRAT (My University, 2026)
Abstract The integration of artificial intelligence into higher education presents both unprecedented opportunities and complex challenges for language learning. This study investigates the effectiveness of ChatGPT as a supplementary tool for enhancing vocabulary development and academic writing style among third-year English as a Foreign Language (EFL) students at the University of Souk-Ahras, Algeria. To address the pedagogical challenges of limited exposure to authentic English and insufficient writing practice, this research adopted a quantitative descriptive design. Data was collected from 50 undergraduate students using a structured questionnaire administered through a custom mobile application. The empirical findings reveal that participants frequently utilize ChatGPT for academic purposes and perceive it as highly effective. Students reported significant improvements in acquiring new academic vocabulary, expanding lexical variety, and avoiding repetition. Furthermore, the tool positively influenced their academic writing style by enhancing structural clarity, coherence, and grammatical accuracy. While participants highlighted benefits in saving time and fostering autonomy, the study also uncovered critical concerns regarding the risk of overdependence, the erosion of critical thinking, and the severe threat of academic plagiarism. Ultimately, the study concludes that while ChatGPT represents a powerful instrument for EFL education, its successful integration requires active pedagogical mediation. Educators and institutions must provide clear ethical guidelines to ensure students use AI responsibly as a supportive resource rather than a replacement for intellectual effort. ------------------------ ملخص يقدم دمج الذكاء الاصطناعي في التعليم العالي فرصاً غير مسبوقة وتحديات معقدة لتعلم اللغات. تبحث هذه الدراسة في فعالية استخدام "ChatGPT" كأداة مساعدة لتعزيز تطور المفردات وتحسين أسلوب الكتابة الأكاديمية لدى طلبة السنة الثالثة في تخصص اللغة الإنجليزية كلغة أجنبية بجامعة سوق أهراس، الجزائر. ولمعالجة التحديات التربوية المتمثلة في قلة التعرض للغة الإنجليزية الأصلية ونقص الممارسة الكتابية، اعتمدت الدراسة منهج البحث الوصفي الكمي. تم جمع البيانات من 50 طالباً باستخدام استبيان مهيكل وُزع عبر تطبيق إلكتروني تكشف النتائج التجريبية أن المشاركين يستخدمون"ChatGPT" بشكل متكرر للأغراض الأكاديمية ويرونه فعالًا للغاية. وأبلغ الطلبة عن تحسن كبير في اكتساب مفردات جديدة، وتوسيع التنوع المعجمي، وتجنب التكرار. علاوة على ذلك، أثرت الأداة إيجابياً على أسلوب كتابتهم الأكاديمية من خلال تعزيز الوضوح الهيكلي، والتماسك، والدقة النحوية. وفي حين أشاد المشاركون بفوائد الأداة في توفير الوقت وتعزيز الاستقلالية، كشفت الدراسة أيضاً عن مخاوف بالغة الأهمية بشأن خطر الاعتماد المفرط، وتراجع التفكير النقدي، والتهديد الخطير للانتحال الأكاديمي. وتخلص الدراسة في النهاية إلى أنه على الرغم من أن "ChatGPT" يمثل أداة قوية للتعليم، إلا أن دمجه بنجاح يتطلب وساطة تربوية نشطة. ويجب على المعلمين والمؤسسات تقديم إرشادات أخلاقية واضحة لضمان استخدام الطلبة للذكاء الاصطناعي بمسؤولية كمورد داعم وليس كبديل للمجهود الفكري. --------------------------- Résumé L'intégration de l'intelligence artificielle dans l'enseignement supérieur présente des opportunités sans précédent ainsi que des défis complexes pour l'apprentissage des langues. Cette étude examine l'efficacité de ChatGPT en tant qu'outil supplémentaire pour améliorer le développement du vocabulaire et le style de rédaction académique chez les étudiants de troisième année d'anglais langue étrangère (EFL) à l'Université de Souk-Ahras, en Algérie. Afin de relever les défis pédagogiques liés à une exposition limitée à l'anglais authentique et à un manque de pratique de l'écriture, cette recherche a adopté une approche quantitative descriptive. Les données ont été collectées auprès de 50 étudiants à l'aide d'un questionnaire structuré administré via une application mobile. Les résultats empiriques révèlent que les participants utilisent fréquemment ChatGPT à des fins académiques et le perçoivent comme très efficace. Les étudiants ont signalé des améliorations significatives dans l'acquisition d'un nouveau vocabulaire, l'élargissement de la variété lexicale et l'évitement des répétitions. De plus, l'outil a influencé positivement leur style d'écriture en améliorant la clarté structurelle, la cohérence et la précision grammaticale. Bien que les participants aient souligné un gain de temps et une plus grande autonomie, l'étude a également mis en évidence des préoccupations critiques concernant le risque de dépendance excessive, l'érosion de la pensée critique et la menace de plagiat académique. En fin de compte, l'étude conclut que bien que ChatGPT soit un instrument puissant, son intégration réussie exige une médiation pédagogique active et des directives éthiques claires pour garantir une utilisation responsable comme ressource de soutien. .
Keywords: Artificial Intelligence (AI); ChatGPT; English as a Foreign Language (EFL); Vocabulary Development; Academic Writing; Educational Technology; Higher Education; الذكاء الاصطناعي، ChatGPT، اللغة الإنجليزية كلغة أجنبية، تنمية المفردات، الكتابة الأكاديمية، تكنولوجيا التعليم، التعليم العالي.; Intelligence artificielle; anglais langue étrangère (EFL); développement du vocabulaire; rédaction académique; technologie éducative; enseignement supérieur